1979
DOI: 10.1107/s0567740879009328
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and X-ray analysis of a 1:1 adduct of hexamethylenetetramine oxide and hydroquinone

Abstract: ExperimentalA 1:1 adduct of hexamethylenetetramine oxide and hydroquinone, (CH2)6N40.C6H4(OH)2, has been prepared and subjected to crystal structure_analysis. The crystals are triclinic, space group P1, with a = 9.532(2), b = 6.521(1), c = 10.399(2) A, a= 102.13 (2), fl = 83.09 (2), y = 92.09 (2) °, and Z = 2. The structure was solved by a combination of direct phasing with packing considerations and refined to R = 0.053 for 2334 Mo Ka diffractometer data. The C6H4(OH)2 molecules occupy two non-equivalent site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…62,63 It is a neutral molecule, though there is a formal charge separation between nitrogen and oxygen. The structure of several adducts of urotropine-N-oxide have also been reported; [64][65][66][67][68] we note that the molecular and crystal structure of 1 was first determined by Mak in 1978, from data accumulated at room temperature. 67,68 There is a potential coupling between the distribution of electron density associated with the hydrogen position and the structure of the formic acid residue in urotropine-N-oxide‚formic acid, and in a valence bond, atomistic description, this correla-tion automatically is present.…”
Section: [T]he Molecular Structure Hypothesissthat a Molecule Is A Co...mentioning
confidence: 80%
See 1 more Smart Citation
“…62,63 It is a neutral molecule, though there is a formal charge separation between nitrogen and oxygen. The structure of several adducts of urotropine-N-oxide have also been reported; [64][65][66][67][68] we note that the molecular and crystal structure of 1 was first determined by Mak in 1978, from data accumulated at room temperature. 67,68 There is a potential coupling between the distribution of electron density associated with the hydrogen position and the structure of the formic acid residue in urotropine-N-oxide‚formic acid, and in a valence bond, atomistic description, this correla-tion automatically is present.…”
Section: [T]he Molecular Structure Hypothesissthat a Molecule Is A Co...mentioning
confidence: 80%
“…It is notable that the N−O bond length is particularly short at 1.3951(12) Å, where the normal range for the N−O distance in hydroxylammonium cations is 1.396−1.436 Å. , It is a neutral molecule, though there is a formal charge separation between nitrogen and oxygen. The structure of several adducts of urotropine- N -oxide have also been reported; we note that the molecular and crystal structure of 1 was first determined by Mak in 1978, from data accumulated at room temperature. ,
1 Molecular structure of urotropine- N -oxide.
…”
Section: Introductionmentioning
confidence: 87%
“…A research program on the structural chemistry of polycyclic tertiary amine N-oxides has been pursued in our laboratory. A series of preparative and X-ray crystallographic studies on the adducts of hexamethylenetetramine N-oxide (HMTO) have shown that all these structures involve hydrogen bonding between the terminal 0 atom of the N + 0 dative bond and the proton donor molecule(s) (7)(8)(9)(10). We now report the synthesis and structural characterization of a series of heterocyclic tertiary amine N,N '-dioxide hydrates, namely N, N '-di(o-toly1)piperazine N,N '-dioxide tetrahydrate, I, N, N '-di(p-toly1)piperazine N, N '-dioxide tetrahydrate, 11, and N,N '-di(p-chloropheny1)piperazine N,Nr-dioxide tetrahydrate, 111.…”
Section: Introductionmentioning
confidence: 99%